Genetics of non‐syndromic and syndromic oculocutaneous albinism in human and mouse. (8th May 2021) - Fernández, Almudena; Hayashi, Masahiro; Garrido, Gema; Montero, Andrea; Guardia, Ana; Suzuki, Tamio; Montoliu, Lluis
Abstract: Oculocutaneous albinism (OCA) is the most frequent presentation of albinism, a heterogeneous rare genetic condition generally associated with variable alterations in pigmentation and with a profound visual impairment. There are non‐syndromic and syndromic types of OCA, depending on whether the gene product affected impairs essentially the function of melanosomes or, in addition, that of other lysosome‐related organelles (LROs), respectively. Syndromic OCA can be more severe and associated with additional systemic consequences, beyond pigmentation and vision alterations. In addition to OCA, albinism can also be presented without obvious skin and hair pigmentation alterations, in ocular albinism (OA), and a related genetic condition known as foveal hypoplasia, optic nerve decussation defects, and anterior segment dysgenesis (FHONDA). In this review, we will focus only in the genetics of skin pigmentation in OCA, both in human and mouse, updating our current knowledge on this subject.